Hedonic test of Lombok Island palm sugar candy formulated with Multi-Purpose Tree Species (MPTS) leaves infusion - Baharudin, Baharudin; Triandini, I Gusti Agung Ayu Hari; Wangiyana, I Gde Adi Suryawan (Journal of Agritechnology and Food Processing, 2023)
The purpose of this research is to conduct a hedonic test of palm sugar candy mix with multi-purpose tree species (MPTS) leaves infusion using various statistical approaches. This research used Arenga pinata sap water as raw material. MPTS leaves infusion is the treatment that was added to a palm sugar candy, including I1= Addition of cacao (Theobroma cacao) leaves infusion, I2 = addition of agarwood (Gyrinops versteegii) leaves infusion, I3 = addition of coffee (Coffea robusta) leaves infusion, I4 = addition of soursop (Annona muricata) leaves infusion. Respondents gave evaluations using a 5-scale hedonic score for the treatments in 3 parameters, including appearance, aroma, and taste. Evaluation scores were analyzed using four statistical approaches: Kruskal-Wallis, Freidman, ANOVA-CRD, and ANOVA-RCBD. The results show that different treatments resulted in significantly different respondent evaluation scores. Treatment I1 has the highest score, while I3 has the lowest score. However, respondents give evaluation scores higher than the threshold value (numeric score >3) in all parameters. This shows that the Addition of MPTS leaf infusion has promising prospects for developing palm sugar candy products. Adding cacao leaves infusion to palm sugar candy can give the highest hedonic score from respondents in all parameters, including appearance, aroma, and taste.